The intergenerational effects of socioeconomic inequality on unhealthy bodyweight - Balasooriya, Namal N; Bandara, Jayatilleke S; Rohde, Nicholas (My University, 2021)
We study the effects of inherited socioeconomic characteristics on markers of unhealthy bodyweight. Taking Australian microdata from 2007 to 2013, we show that approximately 4% of the variation in outcomes is determined by factors beyond an individual's control, such as their race, gender, and social class. Paternal socioeconomic status is the primary explanatory factor, with those born to more affluent fathers slightly less likely to be overweight in adulthood. Decompositions reveal that only 20%-25% of this effect is attributable to advantaged families exhibiting better health behaviors, which implies that unobserved factors also play an important role. Since diseases associated with unhealthy weight place a major strain on public healthcare systems, our results have implications for the provision of treatment when resources are constrained.
Health Economics
Keywords: Health and wellbeing